2019
DOI: 10.1007/s11663-019-01603-2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Segregation of Mn on the Recrystallization Behavior of C-Mn Steels

Abstract: The influence of Mn segregation that occurs during casting on recrystallization kinetics has been explored for a C-Mn automotive steel. A homogenization heat treatment was used to remove Mn segregation, while maintaining a similar initial austenite grain size to the segregated condition, to provide base-line comparison data. Deformation trials were carried out in a Gleeble thermomechanical simulator to 0.3 strains at 900°C, and significant differences in both recrystallization times and final grain sizes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In addition to Equation , Figure shows images taken from the CSLM during cooling of the sample at 1 and 20 °C s −1 . Due to the direction of cooling, the secondary dendrite arms growth is out of the plane imaged (primary dendrite grow parallel to the droplet surface) . Equation predicts the SDAS to be 148 and 47 µm at the 1 and 20 °C s −1 solidification rates, respectively, and Figure shows that these values used are in agreement, with the experimentally determined SDAS being 155 and 42 μm, respectively.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In addition to Equation , Figure shows images taken from the CSLM during cooling of the sample at 1 and 20 °C s −1 . Due to the direction of cooling, the secondary dendrite arms growth is out of the plane imaged (primary dendrite grow parallel to the droplet surface) . Equation predicts the SDAS to be 148 and 47 µm at the 1 and 20 °C s −1 solidification rates, respectively, and Figure shows that these values used are in agreement, with the experimentally determined SDAS being 155 and 42 μm, respectively.…”
Section: Resultssupporting
confidence: 64%
“…Casting and Thermal Profiles A high temperature confocal scanning laser microscope (CSLM) was used to simulate different cooling rates (1 and 20 °C s −1 ) to investigate precipitation in the steel. A full description of how the CSLM works can be found in the literature . For this work, samples of 2 × 2 × 2 mm cubes were prepared and placed in an alumina crucible.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has shown that the surface measurements of SDAS in the CSLM are the same as observed in the bulk material. [19] Figure 2 shows the secondary dendrite arm spacing (SDAS) as a function of the cooling rate and a typical image of the steel surface in the CSLM where the solidifying steel secondary dendrite arm tips can be seen; as the dendrite grow approximately parallel to the steel surface, the spacing between the observed tips gives the SDAS. [19] The SDAS with cooling rate data has been compared to the literature [20] for a similar steel (0.17C-1.5Mn-0.4Si) and good agreement between the two can be seen in Figure 2.…”
Section: A Confocal Microscopymentioning
confidence: 99%
“…Reliable quantitative microstructural data are also required to feed into creep damage models for these materials. [27] It is clear that micro-segregation can have significant effects in other steel types such as those detailed for high-strength low-alloy (HSLA) steels [28][29][30] and in automotive grades, [31] where the effects of segregation on precipitation and grain structure affecting properties and property scatter have been identified. In the case of HSLA steels, a study by Wang et al regarding the segregation of Nb showed a subsequent formation of an increased amount of Nb-rich precipitates in the interdendritic regions resulting in a banded microstructure with a bimodal grain size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Regarding C-Mn automotive steels, Slater et al found a Mn-segregated steel sample which only showed a partially recrystallized microstructure for the same holding times of an unsegregated sample. [31] In both examples, the objective was to investigate the variations in mechanical properties due to inhomogeneous compositions and microstructures. The objective of this paper is to study the implications of micro-segregation of Mo and its effect on the quantification of the intermetallic Laves phase in Cr.91 steel, a key detail that to the author's knowledge has not been previously appreciated or studied.…”
Section: Introductionmentioning
confidence: 99%